Postponement of Fulfillment of Achievements in Business Contracts during the Covid-19 Pandemic as a Basis for Force Majeure - Atika Ismail; Lilies Anisah; Eni Suarti (Global Writing Academica Researching and Publishing, 2022)
The purpose of this journal is to find out the policies of the parties regarding delaying the fulfillment of business contract agreements during the Covid-19 pandemic and to find out the impact of delaying the fulfillment of business contracts for the parties during the Covid-19 pandemic. The research method uses the juridical-normative method. The results of the research method concluded that: 1). If the Covid-19 pandemic is included in a force majeure situation, the parties can take a policy to terminate the agreement if the pandemic is permanent or can delay the fulfillment of achievements if the situation is only temporary. 2). The impact of the current pandemic is that the parties have to temporarily postpone the contract that was agreed before the Covid-19 pandemic occurred due to restrictions on community activities whose rules have been conveyed by the Indonesian government. The delay to fulfill the achievement itself must get approval from both parties so that there is no broken promise (default).